Unconventional monetary policy and the (Neo)Fisher effect: has the federal reserve misunderstood monetary policy? - Andrew Phiri (Cogent Economics & Finance)
The failure of the Federal Reserve Bank to control inflation within its target range has raised concerns about potential misunderstandings in US monetary policy dynamics. The debate revolves around the Fisher effect, a traditional theory, and the NeoFisher effect, a recently proposed alternative theory, in relation to their applicability in the United States. Using wavelet tools and a monthly dataset from 2007:01 to 2023:04, we analyze the Fisher and NeoFisher effects in time-frequency space. Our findings indicate that policy choices significantly influence the behavior of individual time series, with unconventional monetary policy leading to greater variability and traditional policy resulting in weaker variability. Moreover, before the 2013–2014 taper tantrum, significant Fisher (NeoFisher) effects were observed at higher (lower) frequency synchronizations. However, afterward, NeoFisher effects dominate at both lower and higher frequency co-movements. Our results, which are consistent across different measures of nominal interest rates and inflation, bridge the gap between the NeoFisherian theory and empirical evidence, have ramifications for the Federal Reserve Bank’s credibility among economic agents and for Central Banks emulating US monetary policy.